FORMASI DAN REKONSTRUKSI POLITIK ISLAM ABAD 19 - Zaenal Abidin (Universitas Islam Negeri (UIN) Mataram, 2015)
Islamic politics involves contest and competition of interpretation about symbol as control for institution, both formal and informal which depends the symbol. Interpretation about these symbols is influenced by different background because political system in Muslim world or everywhere cannot avoid competition management, so it is always identical with interest. In 1924 AD, institution of Khalifah Islamiyah was removed because in this period religion was truly placed in individual zone, without any intervention from country. Finally Muslims lost their religionpolitics and geo-politics identity, Muslim countries then changed into nation-state model in one nation and one stateknown by secularism and created various kinds of thoughts informulating state principle. Secularism in this meaning is separation between religion and government system. Karl Mark states: first, religion becomes medium of transcendental justification for status quo, by using religion, economical system does not get protest. Second, religion also emphasizes to the transcendental world as fate which must be received by patience, and also must believe about life after death; religion helps to change human attention about physical and material difficulties, as a consequence from secular political modernization, those statements response Muslim reformer figure like: Muhammad Ali Pasya, Jamaludin al-Afgani, Muhammad Abduh, and Rasyid Rida.